2020
DOI: 10.1111/jne.12892
|View full text |Cite
|
Sign up to set email alerts
|

The neurohypophysial oxytocin and arginine vasopressin system is activated in a knee osteoarthritis rat model

Abstract: Osteoarthritis (OA) causes chronic joint pain and significantly impacts daily activities. Hence, developing novel treatment options for OA has become an increasingly important area of research. Recently, studies have reported that exogenous, as well as endogenous, hypothalamic‐neurohypophysial hormones, oxytocin (OXT) and arginine‐vasopressin (AVP), significantly contribute to nociception modulation. Moreover, the parvocellular OXT neurone (parvOXT) extends its projection to the superficial spinal dorsal horn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…S1 online), and mechanical and thermal hyperalgesia were still observed in the SNL. Although the expression of AVP-eGFP, AVP mRNA, and plasma AVP concentration was significantly increased, hyperalgesia persisted in our previous AA model and knee OA model 20 , 22 . We previously reported that AVP and Oxytocin (OXT) exhibited similar kinetics in various pain models 20 , 21 , 25 .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…S1 online), and mechanical and thermal hyperalgesia were still observed in the SNL. Although the expression of AVP-eGFP, AVP mRNA, and plasma AVP concentration was significantly increased, hyperalgesia persisted in our previous AA model and knee OA model 20 , 22 . We previously reported that AVP and Oxytocin (OXT) exhibited similar kinetics in various pain models 20 , 21 , 25 .…”
Section: Discussionmentioning
confidence: 60%
“…AVP-eGFP Tg rats (7 weeks old, weighing 238–305 g) and AVP-hM3Dq-mCherry Tg rats (7 weeks old, weighing 253–350 g) were bred and maintained as described previously 22 , 24 , 51 . All procedures were performed according to the guidelines on the use and care of laboratory animals established by the Physiological Society of Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the six marker genes previously identified, we found that CDKN1A, FOSB, STMN2, and SLC2A3 genes were reported to be associated with cartilage inflammation in OA (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). For example, the expression level of CDKN1A will increase correspondingly during cartilage degeneration (44), IL-17 and IL-1beta induced collagenase-3 production through AP-1 occurred with differential protein complex, and stimulation resulted in FOSB activation (52), STMN2 has significant differences between preserved and subchondral bone (48).…”
Section: Discussionmentioning
confidence: 88%
“…UETA their fluorescence intensities in the soma and number of fluorescent terminals are increased sensitively after physiological and pathophysiological stimuli such as dehydration, 13 chronic salt loading, 32 seizure, 33,34 acute/chronic nociceptive stimuli, [35][36][37][38][39][40][41][42] aging 43 and estrus cycle. 44 In addition, it is known that corticotropin-releasing homrone (CRH)-producing parvocellular neurons in the PVN also synthesize AVP under stressful conditions.…”
Section: Evaluation Of Avp and Oxt Synthesis/ Storage By Fluorescence Intensity: Avp-egfp And Oxt-mrfp1 Transgenic Ratsmentioning
confidence: 99%